Unveiling the seismic sensitivity of the Himalayan tunnels: a comprehensive assessment through analytical and numerical exploration of P-wave dynamics - Ansari, Abdullah; Mandhaniya, Pranjal; Malik, Bilal Ahmad (Frontiers in Built Environment, 2025)
This study investigated the seismic sensitivity of tunnels in the Jammu Region (JR) of the northwestern Himalayas, a region characterized by significant seismic activity and complex geological conditions. The research combined both analytical and numerical approaches to assess the influence of site conditions, tunnel lining, and reinforcement properties on tunnel resilience. A key objective is to develop a more reliable seismic assessment method by adopting a P-wave-based approach, which is particularly suitable for mountainous tunnels prone to landslides. The study identified three seismic hazard zones, with peak ground accelerations (PGA) ranging from less than 0.3 g to greater than 0.5 g, providing vulnerability aspects. The major outcomes of this study include guidelines for the design and retrofitting of sustainable and resilient underground structures in the Himalayas, with broader implications for global projects in seismically active and geologically complex regions. The methodologies and insights can be applied to infrastructure projects worldwide, enhancing the safety of communities living in vulnerable areas. This work aligns with the United Nations Sustainable Development Goals (SDGs), particularly in promoting resilient infrastructure and sustainable development, contributing to both structural resilience and the geological safety of the Himalayan region.